Kadar asam urat pada wanita Indonesia: Peran asupan purin dan usia - Rahmasari, Nisya Cesaryani; Briawan, Dodik; Dewi, Mira (ARGIPA (Arsip Gizi dan Pangan), 2025)
Elevated uric acid levels are a prevalent health issue in women.  A high-purine diet and age are believed to significantly affect uric acid levels, particularly in Indonesian women.  This study seeks to examine the correlation between purine consumption and age concerning uric acid levels in Indonesian women aged 15 to 54 years. This research employed a cross-sectional design involving female participants aged 15 to 54 years from ten provinces in Indonesia.  Uric acid level data were obtained via capillary blood tests administered by competent healthcare professionals. Information on purine consumption and age was collected by interviews utilizing the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) administered by enumerators. Over 25% of the total participants in this study were between the ages of 41 and 54.  In this study, 21.1% of subjects exhibited hyperuricemia, while 1.5% ingested elevated levels of purines.  A substantial link existed between purine intake and age for uric acid levels (p<0.05), with a correlation coefficient of r=0.149; 1.000. Increased consumption of foods rich in purines correlates with a heightened risk of elevated uric acid levels in the bloodstream, which also tend to rise with advancing age.